Impact and overuse injuries in runners - Hreljac, A. (Medicine & Science in Sports & Exercise, 2004)
Forces that are repeatedly applied to the body could lead to positive remodeling of a structure if the forces fall below the tensile limit of the structure and if sufficient time is provided between force applications. On the other hand, an overuse injury could result if there is inadequate rest time between applied forces. Running is one of the most widespread activities during which overuse injuries of the lower extremity occur. The purpose of this article is to review the current state of knowledge related to overuse running injuries, with a particular emphasis on the effect of impact forces. Recent research has suggested that runners who exhibit relatively large and rapid impact forces while running are at an increased risk of developing an overuse injury of the lower extremity. Modifications in training programs could help an injured runner return to running with decreased rehabilitation time, but it would be preferable to be able to advise a runner regarding injury potential before undertaking a running program. One of the goals of future research should be to focus on the prevention or early intervention of running injuries. This goal could be accomplished if some easily administered tests could be found which would predict the level of risk that a runner may encounter at various levels of training intensity, duration, and frequency. The development of such a screening process may assist medical practitioners in identifying runners who are at a high risk of overuse injury.